The Importance of Orientation Guidance in Education and Training Activities - Yiğen, Veysel; Koçoğlu, Erol (The International Society for Technology Education and Science, 2020)
The participation of human beings in social and social activities in society is an important process in terms of socialization. The effective realization of this process can be achieved by the individual's ability to solve adaptive problems. An individual's encounter with orientation problems is closely related to his educational life. Therefore, the trainings that the individual receives for orientation guidance in the education process are very important. The socialization process of the individual can be facilitated or made difficult through educational activities. This situation is commensurate with the competence knowledge of the personnel responsible for the quality of education or training activities. In this study prepared based on qualitative method, scanning model was used. It has been found that activities for orientation guidance that form the subject of the study should be prepared with an approach that takes the student to the center in addition to the dimension of adaptation to the school and rule reminder. As a result of this study, it was concluded that orientation activities also contribute to students' communication and problem solving skills. In the light of the results obtained in the study, suggestions were presented by the researcher. © 2020 Published by ISRES Publishing
Eğitimde Oryantasyon Etkinliklerine İlişkin Öğretmen Görüşleri
International Conference on Research in Education and Science, ICRES 2020 -- 21 March 2020 through 24 March 2020 -- Istanbul -- 187303
Keywords: Compliance; Education; Guidance; Training